The Role of Competition in Increasing The Financial Authority of Joint Stock Companies (International Journal of Scientific Trends, 2024)
This article discusses what is a joint-stock company and the measures currently being taken to increase the financial potential of joint-stock companies and the role of competition in increasing the financial potential of these joint-stock companies.